An Unexpected Diastereoselective Synthesis of Novel Substituted Pyridines via One-Pot, Four-Component Reaction - Zangouei, Mahdieh; Esmaeili, Abbas Ali; Mague, Joel T. (Synlett, 2016)
An efficient diastereoselective approach for the preparation of novel substituted pyridines has been developed through a one-pot, four-component reaction of easily available aromatic aldehydes, malononitrile, and 6,8-dimethyl-2-hydroxy-4H-pyrimido[1,2-a]pyrimidine-4-one, in appropriate alcohols at reflux in the presence of diisopropylethylamine (DIPEA) as organic base catalyst. Unexpected products were obtained in high to excellent yields using a simple workup procedure. The products synthesized showed high diastereoselectivity, and the stereochemistry was confirmed by X-ray diffraction analysis.
Keywords: multicomponent reaction; diastereoselective synthesis; 6,8-dimethyl-2-hydroxy-4H-pyrimido[1,2-a]pyrimidine-4-one; malononitrile; 2-oxo-4-phenyl-1,2,3,4-tetrahydropyridine